Characterising atypical Candida albicans clinical isolates from six third-level hospitals in Bogotá, Colombia (2015)
Background: Candida species are the most frequently found fungal pathogens causing nosocomial disease in a hospital setting. Such species must be correctly identified to ensure that appropriate control measures are taken and that suitable treatment is given for each species. Candida albicans is causing most fungal disease burden worldwide; the challenge lies in differentiating it from emerging atypical, minor and related species such as Candida dubliniensis and Candida africana. The purpose of this study was to compare identification based on MALDI-TOF MS to standard identification systems using a set of nosocomial isolates. Methods: Eleven nosocomial samples were collected from 6 third-level hospitals in Bogotá, Colombia. All the samples were identified by combining MALDI-TOF MS with morphological characters, carbohydrate assimilation and molecular markers (D1/D2 and HWP1). Results: The present work describes the first collection of atypical Colombian Candida clinical isolates; these were identified as Candida albicans/Candida africana by their MALDI-TOF MS profile. Phenotypical characteristics showed that they were unable to produce chlamydospores, assimilate trehalose, glucosamine, N- acetyl-glucosamine and barely grew at 42 °C, as would be expected for Candida africana. The molecular identification of the D1/D2 region of large subunit ribosomal RNA and HWP1 hyphal cell wall protein 1 sequences from these isolates was consistent with those for Candida albicans. The mass spectra obtained by MALDI-TOF MS were analysed by multi-dimensional scaling (MDS) and cluster analysis, differences being revealed between Candida albicans, Candida africana, Candida dubliniensis reference spectra and two clinical isolate groups which clustered according to the clinical setting, one of them being clearly related to C. albicans. Conclusion: This study highlights the importance of using MALDI-TOF MS in combination with morphology, substrate assimilation and molecular markers for characterising Candida albicans-related and atypical C. albicans species, thereby overcoming conventional identification methods. This is the first report of hospital-obtained isolates of this type in Colombia; the approach followed might be useful for gathering knowledge regarding local epidemiology which could, in turn, have an impact on clinical management. The findings highlight the complexity of distinguishing between typical and atypical Candida albicans isolates in hospitals. © 2015 Rodríguez-Leguizamón et al.